Fluorine-18 labelled Ruppert–Prakash reagent ([18F]Me3SiCF3) for the synthesis of 18F-trifluoromethylated compounds. Issue 43 (4th May 2021) - Pees, Anna; Vosjan, Maria J.W.D; Vasdev, Neil; Windhorst, Albert D.; Vugts, Danielle J.
Abstract : The radiolabelling of Ruppert–Prakash reagent with fluorine-18 was developed and applied in the [ 18 F]trifluoromethylation of benzaldehydes, acetophenones and benzophenones. Abstract : This article describes the first synthesis and application of fluorine-18 labelled Ruppert–Prakash reagent [ 18 F]Me3 SiCF3 . [ 18 F]Me3 SiCF3 was synthesized from [ 18 F]fluoroform with radiochemical yields of 85–95% and radiochemical purities of >95% within 20 minutes. 18 F-trifluoromethylated compounds were successfully prepared by reaction of [ 18 F]Me3 SiCF3 with benzaldehydes, acetophenones and benzophenones.